Automated checking system for modular BIM objects - Sun, Hongwei; Kim, Inhan (Journal of Civil Engineering and Management, 2022)
With the increasing popularity of modular buildings, many manufacturers have made BIM objects for use by designers. However, these BIM objects must satisfy specific regulations and requirements, and their quality needs to be verified. In this study, the authors propose an automated checking system for modular BIM object quality verification. The system includes three parts, which are modular BIM object guideline, pre-checking module and automated code checking module. The modular BIM object quality verification system is proposed to be applied to government modular product certification site for checking the modular BIM objects. It is expected that the use of this automated checking system will make it possible to connect users and manufacturers to promote the circulation of modular building products, as well as provide designers with standardized modular BIM objects for design purposes.